The experiences of Red Crescent relief workers during the COVID-19 pandemic in Iran: a qualitative phenomenological study - Minoo Mohammadkhani; Mohammad Sadegh Tavakoli Sani; Arezoo Sarani; Narges Khanjani (BMC, 2023)
Abstract Background The daily increase of infected individuals and mortalities related to COVID-19 in Iran increased public fear and anxiety and affected the job performance of many health workers, including the Iranian Red Crescent Society, as one of the organizations responding to COVID-19. Methods This study aimed to explore the experiences of Red Crescent rescuers, using a qualitative method with an interpretative phenomenological analysis (IPA), and by conducting semi-structured and in-depth interviews with Red Crescent relief workers from Mashhad in September 2020. Participants were selected by purposive sampling. Results Rescuers in the Red Crescent Society, had gained different experiences during the COVID-19 pandemic. The experiences were categorized into four main themes. These main themes were: (1) Psychological disorders, (2) Organizational support (3) Mis-management (both structural and human factors), and (4) Opportunities. Conclusion The COVID-19 epidemic did create unique opportunities to understand the pitfalls of the Red Crescent aid services. Red Crescent rescue workers suffered from psychological symptoms, and mismanagement was also present. Psychological support and organizational improvements should be implemented.